Multiple Equilibria, Contagion, and the Emerging Market Crises - Masson, Paul. (Washington, D.C. : International Monetary Fund, 1999)
The paper surveys the types of models producing multiple equilibria in financial markets. It argues that such models are consistent with observed phenomena, such as the greater volatility of financial asset prices than of macroeconomic fundamentals. Alternative explanations are compared with the stylized facts concerning capital flows, portfolio shifts, and exchange rate crises. Implications for crisis prediction and prevention are then discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet